2010
DOI: 10.1111/j.1610-0387.2010.07513.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of microorganisms in the development of rosacea

Abstract: SummaryRosacea is a chronic cutaneous disorder characterized by centrofacial persisting erythema, telangiectases, papules, pustules, edema, phymas and ocular involvement. Despite being one of the most common skin disorders, its pathogenesis remains unclear and controversial. Although the disease triggering factors are well recognized, the underlying causes of rosacea have not yet been identified. Several different postulates about its pathogenesis can be found in the medical literature. Abnormalities of the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 39 publications
1
43
0
12
Order By: Relevance
“…[25][26][27][28] Based on the different studies to date Lazaridou et al later concluded that due to the high prevalence of anti-Hp antibodies in humans in conjunction with the fact that the antibiotics are effective for both disease entities, it would be very difficult to stratify the population studied against all factors that influence both rosacea and H. pylori infection. 29 Similarly the trend for an increasing prevalence of H. pylori with severity of rosacea is suggested by the study reported by Diaz et al 30 Though the study did not achieve statistical significance a suggestion of a potential positive association between the severity of rosacea and both concurrent H. pylori infection and magnitude of anti-H. pylori CagA antigen humoral immune response was observed .Our study also shows that the mean values of anti H pylori IgG antibodies follow the linear trend. The measures of association was estimated with multiple correlation (R=0.447) showing a positive linear trend and the values increases with the clinical severity of rosacea has been supported statistically (F=5.74, df=1, P=0.025).…”
Section: -4supporting
confidence: 83%
“…[25][26][27][28] Based on the different studies to date Lazaridou et al later concluded that due to the high prevalence of anti-Hp antibodies in humans in conjunction with the fact that the antibiotics are effective for both disease entities, it would be very difficult to stratify the population studied against all factors that influence both rosacea and H. pylori infection. 29 Similarly the trend for an increasing prevalence of H. pylori with severity of rosacea is suggested by the study reported by Diaz et al 30 Though the study did not achieve statistical significance a suggestion of a potential positive association between the severity of rosacea and both concurrent H. pylori infection and magnitude of anti-H. pylori CagA antigen humoral immune response was observed .Our study also shows that the mean values of anti H pylori IgG antibodies follow the linear trend. The measures of association was estimated with multiple correlation (R=0.447) showing a positive linear trend and the values increases with the clinical severity of rosacea has been supported statistically (F=5.74, df=1, P=0.025).…”
Section: -4supporting
confidence: 83%
“…The prevalence of H. pylori infection was found higher in patients with rosacea when compared to the general population, and its eradication has been shown to influence the clinical outcome of this disease (31,39,(44)(45)(46) . However, other studies have not found such difference (41,(47)(48)(49) . Demodex, a microscopic mite found in hair follicles and sebaceous glands, is the most common ectoparasite in humans.…”
Section: Etiology and Pathophysiologymentioning
confidence: 85%
“…Studies support its role in the activation of immune mechanisms in certain subtypes of rosacea, especially papulopustular rosacea (32) . The Demodex count was shown significantly higher in patients with facial rosacea, and a study demonstrated a strong correlation between positive serum immunoreactivity and ocular Demodex infestation in facial rosacea and lid margin inflammation (41,50,51) . Another proposed mechanism is that Demodex mites may act as vectors for other microorganisms such as Bacillus olenorium, which may be responsible for initiation of inflammatory response in rosacea, through production of antigenic proteins and stimulation of Toll-like receptor 2 (TLR2) (23,25,38,42,50) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 96%
See 1 more Smart Citation
“…disorders of the pilosebaceous unit, nutritional and chemical factors and infectious factors (Crawford et al, 2004, Yamasaki & Gallo, 2009. Over a significant period of time, there have been numerous attempts to connect the etiopathogenesis of rosacea with the presence of some micro-organisms on or within the skin (Lazaridou et al, 2011), including Demodex mites and bacteria. It is well established that there is a higher density of Demodex mites in the skin of rosacea patients than control patients but the significance of this has been disputed (Vance, 1986;Bonnar et al, 1993;Erbagci & Ozgöztaşi, 1998).…”
Section: Rosacea: Definition and Epidemiologymentioning
confidence: 99%